2006
DOI: 10.1111/j.1574-6941.2005.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

In situ quantitation of the spatial scale of calling distances and population density-independent N-acylhomoserine lactone-mediated communication by rhizobacteria colonized on plant roots

Abstract: We used computer-assisted microscopy at single cell resolution to quantify the in situ spatial scale of N-acylhomoserine lactone (AHL)-mediated cell-to-cell communication of Pseudomonas putida colonized on tomato and wheat root surfaces. The results of this in situ quantification study on close-to-natural surfaces challenge the conventional view of a quorum group requirement of high cell densities for this type of bacterial communication. In situ image analysis indicated that the effective 'calling distance' o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
128
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(140 citation statements)
references
References 26 publications
10
128
0
Order By: Relevance
“…This process occurs when external signal molecules accumulate sufficiently to affect neighboring cells [4,22,65]. Earlier studies [65] using laser scanning confocal fluorescence microscopy and CMEIAS image analysis indicated that two individual cells (one a producer and the other a sensor) are sufficient to fulfill the quorum requirement for N-acylhomoserine lactone (AHL)-negotiated communication while they colonize plant roots. The "calling distance" between pairs of communicating cells during colonization had a mode of 4-5 µm and extended out to a maximum of 78 μm [65] (equivalent to two people conversing while at opposite ends of a soccer field).…”
Section: Spatial Pattern Analysis and Its Relationship To Microbial Bmentioning
confidence: 99%
See 4 more Smart Citations
“…This process occurs when external signal molecules accumulate sufficiently to affect neighboring cells [4,22,65]. Earlier studies [65] using laser scanning confocal fluorescence microscopy and CMEIAS image analysis indicated that two individual cells (one a producer and the other a sensor) are sufficient to fulfill the quorum requirement for N-acylhomoserine lactone (AHL)-negotiated communication while they colonize plant roots. The "calling distance" between pairs of communicating cells during colonization had a mode of 4-5 µm and extended out to a maximum of 78 μm [65] (equivalent to two people conversing while at opposite ends of a soccer field).…”
Section: Spatial Pattern Analysis and Its Relationship To Microbial Bmentioning
confidence: 99%
“…Earlier studies [65] using laser scanning confocal fluorescence microscopy and CMEIAS image analysis indicated that two individual cells (one a producer and the other a sensor) are sufficient to fulfill the quorum requirement for N-acylhomoserine lactone (AHL)-negotiated communication while they colonize plant roots. The "calling distance" between pairs of communicating cells during colonization had a mode of 4-5 µm and extended out to a maximum of 78 μm [65] (equivalent to two people conversing while at opposite ends of a soccer field). Further geospatial analysis indicated that this process of cell-cell communication is controlled more by cell location within diffusion gradients of the signal molecules made by their neighbors than by a quorum requirement of high population density [65].…”
Section: Spatial Pattern Analysis and Its Relationship To Microbial Bmentioning
confidence: 99%
See 3 more Smart Citations